Exploration of pyrazine-embedded antiaromatic polycyclic hydrocarbons generated by solution and on-surface azomethine ylide homocoupling. Issue 1 (December 2017) - Wang, Xiao-Ye; Richter, Marcus; He, Yuanqin; Björk, Jonas; Riss, Alexander; Rajesh, Raju; Garnica, Manuela; Hennersdorf, Felix; Weigand, Jan; Narita, Akimitsu; Berger, Reinhard; Feng, Xinliang; et al.
Abstract Nanographenes, namely polycyclic aromatic hydrocarbons (PAHs) with nanoscale dimensions (>1 nm), are atomically precise cutouts from graphene. They represent prime models to enhance the scope of chemical and physical properties of graphene through structural modulation and functionalization. Defined nitrogen doping in nanographenes is particularly attractive due to its potential for increasing the number of π-electrons, with the possibility of introducing localized antiaromatic ring elements. Herein we present azomethine ylide homocoupling as a strategy to afford internally nitrogen-doped, non-planar PAH in solution and planar nanographene on surfaces, with central pyrazine rings. Localized antiaromaticity of the central ring is indicated by optical absorption spectroscopy in conjunction with theoretical calculations. Our strategy opens up methods for chemically tailoring graphene and nanographenes, modified by antiaromatic dopants. Polyaromatic hydrocarbons can be precisely manipulated to yield ever more complex and discrete graphene analogs, such as nanographenes. Here, the authors use azomethine ylide homocoupling to insert an antiaromatic pyrazine ring into the core of a nanographene, and characterize the molecule's unique electronic character.